The anterolateral complex of the knee: results from the international ALC consensus group meeting - Getgood,A; Brown,C; Lording,T; Amis,AA; Claes,S; Geeslin,A; Musahl,V (Knee Surgery, Sports Traumatology, Arthroscopy, 2019)
The structure and function of the anterolateral complex (ALC) of the knee has created much controversy since the ‘re-discovery’ of the anterolateral ligament (ALL) and its proposed role in aiding control of anterolateral rotatory laxity in the anterior cruciate ligament (ACL) injured knee. A group of surgeons and researchers prominent in the field gathered to produce consensus as to the anatomy and biomechanical properties of the ALC. The evidence for and against utilisation of ALC reconstruction was also discussed, generating a number of consensus statements by following a modified Delphi process. Key points include that the ALC consists of the superficial and deep aspects of the iliotibial tract with its Kaplan fibre attachments on the distal femur, along with the ALL, a capsular structure within the anterolateral capsule. A number of structures attach to the area of the Segond fracture including the capsule-osseous layer of the iliotibial band, the ALL and the anterior arm of the short head of biceps, and hence it is not clear which is responsible for this lesion. The ALC functions to provide anterolateral rotatory stability as a secondary stabiliser to the ACL. Whilst biomechanical studies have shown that these structures play an important role in controlling stability at the time of ACL reconstruction, the optimal surgical procedure has not yet been defined clinically. Concern remains that these procedures may cause constraint of motion, yet no clinical studies have demonstrated an increased risk of osteoarthritis development. Furthermore, clinical evidence is currently lacking to support clear indications for lateral extra-articular procedures as an augmentation to ACL reconstruction. The resulting statements and scientific rationale aim to inform readers on the most current thinking and identify areas of needed basic science and clinical research to help improve patient outcomes following ACL injury and subsequent reconstruction.